Epizootic Situation on Helminthosis of Cattle of Public and Private Sectors in the Vologda Region - A. L. Kriazhev (Российский паразитологический журнал)
The purpose of the research is carrying out ecological and epidemical monitoring of helminthosis of cattle of public and private sectors in Vologda region.Materials and methods. Statistical analysis of veterinary reports was conducted according to the form 1Vet-A of the Veterinary medicine administration with State veterinary inspectorate in Vologda region for the period of 2013–2018. The degree of infection by helminths was also analyzed in animals of public and private sectors.Results and discussion. Cattle helminthosis is widely distributed in Vologda region. Helminthosis, which are recorded in cattle constantly and which have high rate of prevalence, were adjusted. Fasciolosis, paramphistomatosis, moniezosis, dictyocaulosis, strongyloidosis are registered in public and private sectors practically annually. What is more, the degree of infection is differing in public and private sectors; the highest parameter of incidence rate is registered in private sector. In conclusion, epizootological monitoring shows specific view on epidemic situation in Vologda region on major cattle helminthosis.